Clinic of acute spinal cord trauma - Trelles, J. O. (1952)
Within the spinal surgical conditions, traumatic occupy a special place. They can result from injury to the bone and disc elements of the spine or spinal and roots; But just as there are no obvious bone lesions bone disorders or neural elements may be directly affected the latter without encountering evidence of bone injury, I often, however, is that injuries occur both items at once.